An uncommon cause of back pain in pregnancy. Issue 951 (7th January 2005) - Vadivelu, R; Green, T P; Bhatt, R
Abstract : Back pain is a major cause of disability worldwide. A case of a 29 year old Caucasian woman with low back pain secondary to an uncommon benign condition called osteitis condensans ilii is presented and the literature is reviewed. Limited information in the literature combined with poor awareness across the specialty and among the primary care physicians leads to an extensive investigation and misdiagnosis of this benign condition. This report emphasis the salient features and the differential diagnosis in diagnosing and managing this rare condition.